A prehistoric houshold (AMTh, 2019)
: 다ιμήν. Από τη στιγμή που έρχεται ένα έργο, ξεκίνησε να μιλήσει. Από αυτό το σημαντικό πράγμα είναι πόσο καλύτερα μπορεί ο αρχαιολόγος να το ακούει. Όλη η information has to come from these deaf and dumb objects. And this is the challenge. These objects are open to a wide range of interpretations. A conversation about this would be very interesting. But before we get to where we really can listen to the language of these deaf and dumb objects, we have to do the research. Excavation research at a site reflects a reality thousands of years old. Before we get there, we have to open up the earth to descend through the millennia, to remove the soil. Excavation is, I'd liken it to a surgical operation, so we need to carry out this operation in order to record the actual state of things. At any prehistoric excavation, things are not revealed in what one would call a narrative form. In a prehistoric excavation, things are not revealed in what one would call a narrative form. They're completely torn apart from one another. So there's the problem. How can the archaeologists intervene so as to fill this chaos opened up not by an earthquake, but by an excavation with the flowers of interpretation? There's a more general problem connected with interpretation. How do we interpret things? Some people say, ''You archaeologists have so much imagination.'' I don't think we do. The archaeologists' imagination, or what people call imagination, is inspired by the things themselves. And we have to take a position. I don't like this comparison, but I think we need to put ourselves in the place of a detective. Objects which are superficially the same, which we see as a series, a continuation, which we consider exactly alike. These objects can be completely different and have different meanings. From that point on, it's not just the scholarly qualifications of an archaeologist that play a role. An archaeologist has to be an extremely gentle human being. When we say someone is a good excavator, we should think of someone who lives in very close contact with life itself. Finds are not just cold, indifferent objects. Vases, tools, objects. One could say that these make up a series of human cries. ''I'm hungry.'' ''Thanks be to God, I'm full.'' ''I'm thirsty, I'll drink some water.'' One question the public asks is, ''What do archaeologists find?'' ''What are these finds?'' Anything and everything constitutes a find for the archaeologists and the student of cultures. I'd say the most important thing is to find out what a find is. I'd say that the find is a piece of information, but that when it's incorporated into a world of other finds, it becomes knowledge. First off, we could say that archaeologists find objects. They find houses. A house area can constitute information. First off, people need to know that a prehistoric household, we're speaking of prehistory, is not found exactly in the form an archaeologist would like it to be. So the first step is for us to reconstruct the household. And within that reconstruction, things assume their proper place. The Neolithic house was constructed of perishable materials. In Macedonia, it was usually made of wood, covered by wattle and daub. The floor's been identified. There's a small oven. Two or three rooms in a row. Next to the oven were preserved some small clay tables, a number of bowls. One looks like it must have been where they needed their bread, a bench, and on top of it, the grindstone, to make flour from wheat. In front of the oven are traces of fire, ashes, and lots of pottery. This is a place where people lived, slept, ate, things like that. And in these houses, we find very simple furnishings. We find ovens in Macedonia, in Thrace. Throughout the Balkans, we constantly find ovens, hearths. These are the sorts of things prehistoric archaeologists find every day. Ovens, hearths, tools, walls. Jars, storage jars in a row. A great moment. It's the moment when prehistoric people decided to produce a jar for storing things. This means it's the moment of surplus, which in the end led prehistoric humans to produce surpluses intentionally, either for exchange or sale. That is, I think it's when the economy starts to become commercialized. The question we're dealing with, since we're talking about a space four by five, let's say, where did people sleep if they slept there? And now one begins framing theories. One starts to create theories. Maybe they were on an upper floor. Maybe the pots which had fallen on this fell from shelves, and they made up their beds on the floor and slept on the floor. This is knowledge I don't know if we'll ever have. What emerges from these objects we find is that food was prepared in the house, provided sustenance, because the storage vessels contain spare foodstuffs. The cooking ware provided for food preparation. They ate there and they probably slept there. And we can hypothesize that we're speaking about families, that is about groups of two, three, four or five people, small family units like ours. The presence of children emerges from the clay nursing bottles. We're speaking of vessels made especially for children, or at any rate, that's how we interpret them. These are the same pots they used to bring us from the religious festivals back then. The little jugs would drink water from as children. It's a tradition which has survived down through the centuries. The pot is the gold of prehistory. Since each era is characterized by a material, I think that pottery characterizes prehistoric civilization. In the Neolithic era in particular, we observe a truly amazing production of pottery. Consider what one did with a pot. Eating, storing, cooking, carrying water. If you want, you could say that they put whatever they needed or whatever they didn't need in a pot. I don't think there was a moment in prehistoric man's life that wasn't connected with pottery, with the pot. So that's the inorganic materials, the hard remains, pottery, stone. All this we can lay hold of, but what about the organic remains from these cultures? I mean, all we know of a Neolithic house is the traces of its piles. In the best case scenario, if there's some charred wood preserved, the pottery, the stone tools, the bones. But what about the woven materials, the baskets, the ropes, the leather goods? All these objects have been lost. But they've left traces. Okay, archaeology started out as the history of art and masterpieces. Now we've come to the point of identifying, in the bottom of pots, the remains from the food these people ate. Even if they lived differently, their way of life was the same as ours. There are some universals about human beings. Hunger is not only the people in Despillio or Tumba or Sesklo. They weren't the only ones who were hungry. Everyone in the world gets hungry. And so the need to deal with hunger is the same, in Mexico or Nepal or in Tokyo. And therefore we have a means of interpreting a phenomenon like this, when it's related to a universal human trait. People were the same. They were just like us, with the same abilities and the same flaws. They were capable of constructing very fine tools. They were capable of building houses. They had unique technical skills. They didn't have computers, but they had other things. Things we could say were comparable, as well as impressive craftsmanship in some fields. But in contrast, they were just as foolish as we are. And they were capable of going to war for any reason or cause. The needs remain the same. The need for a roof to cover one's own and one's family's head. The need to construct tools to shape the space around one. The need to express oneself symbolically, to have some connection with what one doesn't comprehend. There are all these concerns. The fear of death. It's a window into the soul of modern humans. A soul which hasn't changed in essentials from the first goals and first fears humans had. To secure food, a shelter. To comprehend the unknown, to protect themselves from the idea of death. To be continued...